Clinical observation of anaphylaxis after treated with Sweet BV - Ki Rok Kwon; Kye Sung Kang; Kwang Ho Lee; Chung San Lim; Heesun, Jeong; Haeyon, Kwon (Korean Pharmacopuncture Institute, 2009)
Objectives : Sweet bee venom(SBV) is pure melittin, the main component of bee venom, made by removing another components through gel filtration chromatography and propionic acid/urea polyacrylamide gel electrophoresis. In the using SBV, 2 patients were experienced anaphylaxis by SBV. So, we reported the process of anaphylaxis and consider these situation. Methods : We observed 2 patients suffered from anaphylaxis after treated with SBV in the Korean Medical Hospital, Sangji University. Results : Though SBV was removed allergen from bee venom, it is not possible to complete prevention of anaphylactic shock in the clinics. So, Korean medical doctor using BV or SBV must be prepare the system consider a countermeasure by anaphylaxis.